DISTRIBUTED CONGESTION-AWARE TRAFFIC LOAD BALANCING SCHEMES FOR ROUTING IN WIRELESS SENSOR NETWORKS - CHUGHTAI, HAFIZ MUHAMMAD OMER (2016)
Efficient routing m Wireless Sensor Network (WSN) plays an important role in enhancing the performance of the network. The data traffic generated by the sensing nodes in WSN usually follows the shortest discovered route between the source and the sink. If a discovered route is selected more often than other available routes then congestion could occur which not only causes severe information loss, but also leads to faster energy depletion of the sensor nodes. On-demand routing protocols discover the ETE route based on the defined routing criterion, when a route is required. To avoid congestion in WSN, most of the on-demand routing protocols replace only the routing metric and keep the route discovery mechanism intact. Additionally, the solutions to avoid and overcome congestion select the sensor nodes with sufficient buffer space and adjust the traffic rate at the source.